Cadmium Removal with Mutant Brevibacillus Agri C15 Cdr Entrapped in Calcium Alginate Gel: a New Process. Issue 1 (May 2021) - Jebril, N.; Boden, R.; Braungardt, C.
Abstract: With large-scale mining and industrial use of cadmium (Cd), contamination with this metal increased steadily, concerns due to its toxicity and potential damage to the environment and human health have led to the introduction of legislation that regulates acceptable environmental concentrations in different contexts. Therefore, many treatment methods for water and soils have been developed to limit the concentration of Cd in the environment and comply with regulations. In this study, a small laboratory bench-scale column reactor was constructed, optimised, and used to evaluate the removal of Cd from artificial groundwater (AGW) with mutant Brevibacillus agri C15 Cd R and its wild type B. agri C15 entrapped in calcium alginate beads at different Cd concentrations. The morphological properties of the beads were studied by scanning electron microscopy (SEM), and energy-dispersive X-ray (EDX) spectroscopy and the location of Cd adsorbed in the beads was detected using a dithizone histochemical method. The experimental results showed that the mutant had significantly higher removal rates than its wild type B. agri C15 (9 and 5 nmol per day per gram of biomass, respectively) due to the presence of the Cd-dithizone complexes on the bead containing the mutant, compared with the less presence of these complexes on the beads containing the wild type. In conclusion, a new process was developed that achieved higher Cd removal rate from AGW by the mutant B. agri C15 Cd R . In addition, an alternative detection method of Cd (Cd-dithizone complexes) was introduced that showed that Cd was distributed throughout the Cd-loaded beads.